Metode Cluster Hirarki pada Data Margin Perdagangan dan Pengangkutan Komoditas Strategis di Indonesia Tahun 2021 - Erna Suprihartiningsih; Sri Juli Asdiyanti Samuda (Ecoplan, 2023)
This study aims to compare the hierarchical cluster analysis method to classify the value of trading and transportation margin (MPP) into three groups, each with specific characteristics for each commodity strategy. Cophenetic correlation analysis shows that the average hierarchical cluster method is the best for classifying strategic commodity MPPs in Indonesia in 2021. Cluster 1 has moderate characteristics (MPP) for shallots, rice, and purebred chicken. At the same time, Red Chili has low MPP characteristics in this cluster. Hopefully, this study can help policymakers make strategic decisions to reduce commodites’s MPP in provinces which includes clusters 2 and 3 belonging to the high MPP so that the distribution pattern can be more efficient.